The relative stabilities of cyclic dicationic derivatives of diphosphanes with three (3P) or four (4P) linked phosphorus atoms. - Bashforth, R; Boyall, A; Coffer, P; Dillon, K; Goeta, A; Howard, J; Kenwright, A; Probert, MR; Shepherd, H; Thompson, A (2012)
Reaction of a diphosphane with a chlorophosphane in the presence of SnCl(2) or AlCl(3) leads to the formation of dicationic heterocycles with three (3P) or four (4P) linked phosphorus atoms. Some 3P derivatives with small alkyl substituents may also be prepared by direct alkylation of cyclic triphosphenium ions. Several new species were prepared in solution, some of which were isolated and characterised by single-crystal X-ray diffraction. Investigations into the factors favouring formation of 3P or 4P species are described.